COVID-19, Race, and Redlining - Graziella Bertocchi; Arcangelo Dimico (Global Labor Organization (GLO), 2020)
Discussion on the disproportionate impact of COVID-19 on African Americans has been at center stage since the outbreak of the epidemic in the United States. To present day, however, lack of race-disaggregated individual data has prevented a rigorous assessment of the extent of this phenomenon and the reasons why blacks may be particularly vulnerable to the disease. Using individual and georeferenced death data collected daily by the Cook County Medical Examiner, we provide first evidence that race does affect COVID-19 outcomes. The data confirm that in Cook County blacks are overrepresented in terms of COVID-19 related deaths since|as of June 16, 2020|they constitute 35 percent of the dead, so that they are dying at a rate 1.3 times higher than their population share. Furthermore, by combining the spatial distribution of mortality with the 1930s redlining maps for the Chicago area, we obtain a block group level panel dataset of weekly deaths over the period January 1, 2020-June 16, 2020, over which we establish that, after the outbreak of the epidemic, historically lower-graded neigh- borhoods display a sharper increase in mortality, driven by blacks, while no pre- treatment differences are detected. Thus, we uncover a persistence in uence of the racial segregation induced by the discriminatory lending practices of the 1930s, by way of a diminished resilience of the black population to the shock represented by the COVID-19 outbreak. A heterogeneity analysis reveals that the main channels of transmission are socioeconomic status and household composition, whose in uence is magnified in combination with a higher black share.
Keywords: I14; J15; N32; N92; R38; 330; COVID-19; deaths; blacks; redlining; vulnerability; Cook County; Chicago